Development of active shielding gamma probe: a simulation study - Kolcu, O. B.; Yetkin, T.; Iren, E. (SPRINGER HEIDELBERG, 2023)
The aim of the present study is to evaluate a gamma probe with active shielding by using GEANT4 simulation framework. We used BGO scintillators both for gamma detection and active shielding from a point radioactive source, namely 140 keV gammas from Tc-99m. All scintillators were coupled to the silicon photomultipliers with an active area of 3 x 3 mm(2). The response of the gamma probe to radiation was simulated using the optical photon transportation available in the GEANT4 package. We used the simulation results to determine the sensitivity, spatial and angular resolution, and shielding efficiencies in the air and scattering medium for the proposed gamma probe model according to NEMA NU 3-2004 standards. The ability of the probe to find the direction of emission was also evaluated. The sensitivity of the probe was found between 1262 -42284 cps/MBq in the scattering medium based on two scenarios based on active shielding use. In terms of FWHM, the spatial resolution in scattering medium at 30 mm source-to-probe distance was 31 mm and the angular resolution at the same distance was 59?. The shielding effectiveness of the probe was in the range of 89.90 +/- 0.65% and 97.20 +/- 0.19%. The emission directions of gammas were found with an error of less than 8 degrees.
Keywords: SILICON PHOTOMULTIPLIER; BREAST-CANCER; NODE BIOPSY; SENTINEL; Physics